The clinical approach to child and adolescent patients with lipodystrophy: a series of international case discussions - Brown, Rebecca J.; Akinci, Baris; Al Yaarubi, Saif; Bismuth, Elise; Cappa, Marco; Deeb, Asma; Kamrath, Clemens; Musso, Carla; Patni, Nivedita; Prodam, Flavia; Williams, Rachel; Wabitsch, Martin (Frontiers in Endocrinology, 2025)
IntroductionLipodystrophy syndromes comprise a group of rare endocrine disorders characterized by the generalized or partial loss of adipose tissue. Affected individuals frequently display absolute or relative reductions in leptin, a key adipokine regulator of hunger-satiety signaling, and are predisposed to a range of metabolic and end-organ complications, often from a young age. The presentation and severity of lipodystrophy syndromes is largely dependent on the extent of adipose tissue loss while comorbidities often deteriorate with age. In this regard, optimizing care for children and adolescents with lipodystrophy syndromes is a pivotal step in supporting them into adulthood. To assist clinicians with limited experience of managing young patients with lipodystrophy syndromes, we describe our clinical approach to a series of pediatric patients with these rare diseases.MethodsThe clinical history, diagnosis, disease management and follow-up care of 10 international pediatric patients with lipodystrophy syndromes are presented. Teaching points from each case study are also provided. Most of these cases are based on patients from our clinics with certain details changed to protect privacy. Others represent hypothetical scenarios based on our clinical experience supported by review of the medical literature and are included here for educational purposes.ResultsOur patients illustrate the broad phenotypic spectrum of lipodystrophy syndromes that can manifest early in life. We highlight the importance of timely and accurate diagnosis in guiding early disease management strategies to help reduce the risk of comorbidities. The challenges faced by clinicians managing pediatric patients with lipodystrophy syndromes and how these challenges may differ from adult patients are also explored.DiscussionThe cases presented in this manuscript may assist clinical teams to promptly diagnose and holistically manage young patients with lipodystrophy syndromes and help optimize clinical outcomes as they transition to adult care.